PROBLEMATIC QUESTIONS OF CRIMINALISTIC EXPERTISE OF COLD-STEEL ARMS - P. N. Mazurenko (Russian Journal of Economics and Law, 2007)
In the article on the basis of judicial-investigating and expert practice problem issues of criminalistic expertise of cold-steel arms are considered. The author suggests to reconsider the whole complex of regulatory and legal acts, regulating turnover of cold-steel arms and dangerous things, in the first place, existing system of cold-steel arms certification.